A case of otitis media with ANCA-associated vasculitis accompanied with pituitary mass successfully treated by corticosteroids. Issue 2 (3rd July 2018) - Takahashi, Hidenori; Tsuboi, Hiroto; Umeda, Naoto; Toko, Hirofumi; Honda, Fumika; Ohyama, Ayako; Abe, Saori; Yokosawa, Masahiro; Asashima, Hiromitsu; Hagiwara, Shinya; Kondo, Yuya; Matsumoto, Isao; et al.
Abstract: Otitis media with anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (OMAAV) is a new disease entity characterized by progressive sensorineural hearing loss and intractable otitis media against antibiotics and tympanic tube insertion accompanied with ANCA positivity. A 65-year-old woman developed progressing hearing loss, saddle nose, and left facial nerve palsy accompanied with a non-functional pituitary mass and positivity for myeloperoxidase (MPO)-ANCA. She was diagnosed with OMAAV and probable granulomatosis with polyangiitis. Otitis media and hearing acuity were improved and the pituitary mass disappeared after a 40 mg/day course of prednisolone. This is a rare case of OMAAV accompanied with non-functional pituitary mass.